The trauma and the triumph : gender and partition in eastern India - Bagchi, Jasodhara; Dasgupta, Subhoranjan (Stree ; Distributed by Popular Prakashan, 2009)
Contributed articles on the sufferings of women during the partition of Bengal in 1947; includes personal narratives.